Insight Into the Formation of Lithium Alloys in All-Solid-State Thin Film Lithium Batteries - Damian Goonetilleke (Frontiers in Energy Research, 2018)
Solid-state thin film batteries utilize electrode and electrolyte components which are nanometers or micrometers thick, enabling the production of novel devices with new form factors. Here, in situ X-ray diffraction is used to carry out the first study of a solid-state thin film lithium-ion battery containing a solid-state LiPON electrolyte and Bi negative electrode. The structure-electrochemistry relationships in the Li-Bi system are revealed and details of cell construction, data collection, and data analysis is presented to guide for research.